PEMANFAATAN TEKHNOLOGI INFORMASI DAN KOMUNIKASI DALAM MANAJEMEN SEKOLAH DI SMAN 1 SUMENEP - Azis, Abdul (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2018)
he development of information and communication technology with educational institutions to be able to adapt both in management and learning process, so that there is effectiveness and efficiency in achieving educational goals.The aims of this study is to reveal the use of information and communication technology in managing schools in Sumenep 1 High School by using a phenomenological qualitative approach. The results show that the use of information and communication technology can be grouped into two, namely applications developed by the provincial government and applications developed by the school itself. The obstacles faced in the use of information and communication technology are limited to the lack of technology management personnel and limited facilities and infrastructure.